Pembelajaran Berbasis Inkuiri dalam Meningkatkan Keterampilan Berpikir Kritis pada Siswa Kelas 10 dalam Mata Pelajaran Ilmu Sosial - Jennifer Vega (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
Recognizing the persistent challenges students face in analyzing social issues, this study investigated the effectiveness of Inquiry-Based Learning (IBL) in enhancing the critical thinking skills of Grade 10 students in Social Studies at Camaya-an National High School, Loboc, Bohol during the School Year 2025– 2026. Employing a mixed-methods design, the research integrated quantitative and qualitative approaches to measure both academic performance and students’ learning experiences. The quantitative phase involved pre-test and post-test assessments on three key competencies in Araling Panlipunan 10— globalization, labor issues, and migration—revealing significant improvements in students’ post-test scores, with weighted means ranging from 13.29 to 14.17 and p-values below 0.05. Effect sizes (0.45–0.93) indicated moderate to strong impacts of IBL on student learning. The qualitative findings complemented these results, revealing four major themes: Active Engagement and Curiosity, Analytical and Evaluative Thinking, Collaboration and Communication, and Self- Reflection and Independent Learning. These insights demonstrated that IBL promotes higher-order thinking, collaborative inquiry, and self-directed learning. Overall, the integration of both data sets confirmed that IBL is an effective and learner-centered approach that strengthens students’ mastery of concepts, critical reasoning, and engagement in Social Studies. The study recommends continuous teacher training, administrative support, and curriculum integration of IBL to sustain the development of students’ critical thinking skills.